Wideband self‐packaged antenna based on substrate‐integrated suspended line platform for 5G millimeter‐wave application. Issue 12 (1st September 2021) - Wang, Xiyao; Luo, Yu; Ma, Kaixue; Yang, Wanchen; Xue, Quan; Che, Wenquan
Abstract: A wideband antenna based on substrate‐integrated suspended line (SISL) platform is presented for the fifth generation (5G) communication applications. The antenna is composed of two dipoles and differentially driven by coupled slot between dipole arms to achieve symmetrical radiation pattern on both E and H plane. Combining with the multilayer feature of the SISL, a metallic cavity under the dipole is formed to improve the antenna bandwidth and radiation performance. To verify the proposed antenna, one prototype was fabricated using the conventional printed circuit board process and a balun structure was designed to provide the differential excitation. The measured results indicate that the proposed dipole antenna with differential feeding network achieves a large −10 dB impedance bandwidth of 58% from 24.5 to 44.5 GHz and a peak gain of 8.2 dBi. The proposed antenna is a promising candidate for 5G communications due to its advantages of wideband, high gain, low cost, and convenient integration with differential active circuits.